Gamification in EFL classroom to support teaching and learning in 21st century - Redjeki, Indah Sri; Muhajir, R. (JEES (Journal of English Educators Society), 2021)
In the 21st century, the use of games becomes a trend within adults and youngsters and has recently obtained a massive notice of academics, educators, and practitioners. Gamification is a term used in learning with games that can be used to improve English since it reflects an innovative and captivating learning activity. Several studies on gamification show that it can make students feel more excited and motivated during their effort to elevate their English language skills. In this research, one medium of gamification called Duolingo was explored in grammar learning activities for the second-year students in the subject of “Grammar for Written Discourse”. They used Duolingo from their smartphones to support their grammar learning. This research employed an action research design in which observations, questionnaires, and documentation were used to collect the data. By the end of the result, it can be concluded that Duolingo is a medium that can be effectively used to implement gamification in language learning. It is also confirmed that students gave positive attitudes and results in the implementation of Duolingo in grammar lesson. The results of the research can be used as a reference in facilitating the students with innovative and captivating English learning. HIGHLIGHTS: Duolingo provides some language skills that students can improve: grammar, writing, translating, listening, and pronunciation. However, all respondents assumed that the application was more suitable for grammar since Duolingo gives the right answers and repetitions for the wrong answers. Duolingo understands Indonesian words and automatically correct the wrong words.